When to blink and when to think: preference for intuitive decisions results in faster and better tactical choices - Raab, M.; Laborde, S. (Research Quarterly for Exercise and Sport, 2011)
Intuition is often considered an effective manner of decision making in sports. In this study we investigated whether a preference for intuition over deliberation results in faster and better lab-based choices in team handball attack situations with 54 male and female handball players of different expertise levels. We assumed that intuitive choices - due to their affective nature - are faster when multiple options are to be considered. The results show that athletes who had a preference for intuitive decisions made faster and better choices than athletes classified as deliberative decision makers. It is important that experts were more intuitive than near-expert and nonexpert players. The results support a take-the-first heuristic defining how options are searched for, how option generation is stopped, and how an option is chosen. Implications for the training of intuitive decision making are presented.